2015
DOI: 10.1056/nejmoa1510764
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Validation of a 21-Gene Expression Assay in Breast Cancer

Abstract: BACKGROUND Prior studies with the use of a prospective–retrospective design including archival tumor samples have shown that gene-expression assays provide clinically useful prognostic information. However, a prospectively conducted study in a uniformly treated population provides the highest level of evidence supporting the clinical validity and usefulness of a biomarker. METHODS We performed a prospective trial involving women with hormone-receptor–positive, human epidermal growth factor receptor type 2 (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
1,009
4
43

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,191 publications
(1,081 citation statements)
references
References 36 publications
25
1,009
4
43
Order By: Relevance
“…At the time of the interviews, the preliminary results of tailorx 29 were not available. Early results from that trial demonstrated that patients who had a very low recurrence score (0-10) and who received endocrine therapy alone (that is, no chemotherapy) experienced very low recurrence rates at 5 years 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of the interviews, the preliminary results of tailorx 29 were not available. Early results from that trial demonstrated that patients who had a very low recurrence score (0-10) and who received endocrine therapy alone (that is, no chemotherapy) experienced very low recurrence rates at 5 years 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Early results from that trial demonstrated that patients who had a very low recurrence score (0-10) and who received endocrine therapy alone (that is, no chemotherapy) experienced very low recurrence rates at 5 years 29 . Had those results been available, participants might have had a different view of the evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective data from randomized trials (MINDACT, TailorX, X-PONDER, PLAN B) are awaited to assess the prognosis and benefit of chemotherapy according to age and tumor biology in the modern era. In the post-BCY2 preliminary report of the TailorX trial, young women were <5% of the total 50 . Thus, these tests should be used with caution in young women.…”
Section: Adjuvant Systemic Treatment (Table 6)mentioning
confidence: 99%
“…The ability of Oncotype dx to identify a very low-risk population (rate of freedom from distant recurrence at 5 years: 99.3%; 95% confidence interval: 98.7% to 99.6%) has been confirmed by an interim analysis from a prospective trial 25 . Although the Oncotype dx, Prosigna, and EndoPredict assays have all shown that, in the absence of chemotherapy treatment, patients stratified as low risk have a low risk of recurrence, prospective validation data are limited.…”
Section: Predictive Ability Of Multigene Profiling Assays With Respecmentioning
confidence: 94%
“…Accrual for tailorx is complete, but final results have not been published. A recent preliminary report provided data concerning survival and the rate of freedom from distant recurrence for the 1626 low-risk patients who received endocrine monotherapy 25 . Given that the preliminary report provided data only for the low-risk cohort, the reviewers did not believe that those data yet provide level IA evidence for the prognostic ability of Oncotype dx.…”
Section: Study Categoriesmentioning
confidence: 99%